2018
DOI: 10.33425/2639-9490.1024
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Forensic Odontology as Future Perspective among Private Dental Practitioners of Ahmedabad, Gujarat: A Cross-Sectional Study

Abstract: Background: Forensic Odontology is based on fact that, the natural teeth can withstand degradation from extreme conditions even after the death of an individual. Hence, teeth are considered to be very crucial for identification during the investigative procedures, especially when there is lack of any other evidence. Aims: To analyze the level of awareness, feasibility and future perspective of Forensic Odontology among private dental practitioners of Ahmedabad City, Gujarat. Materials and Methods: It is a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The knowledge and attitude towards forensic odontology was studied among practicing dentists and it was found that there was adequate knowledge but less actions and steps taken in this field and a large set of variations seen in the practices in these cases among the dentists. (32). A cross sectional study was done among dentists about forensic odontology as a major tool to mass victim identification and it was found that more awareness needs to be provided about their importance and knowledge regarding this field.)…”
Section: (Akhila Et Al )mentioning
confidence: 99%
“…The knowledge and attitude towards forensic odontology was studied among practicing dentists and it was found that there was adequate knowledge but less actions and steps taken in this field and a large set of variations seen in the practices in these cases among the dentists. (32). A cross sectional study was done among dentists about forensic odontology as a major tool to mass victim identification and it was found that more awareness needs to be provided about their importance and knowledge regarding this field.)…”
Section: (Akhila Et Al )mentioning
confidence: 99%
“…A diferencia de Sheth 15 que encontraron una actitud positiva con una puntuación de 90.85%, probablemente en el programa académico de sus universidades estén implementadas las capacitaciones con respecto al tema sobre el manejo odontológico de pacientes con VIH, por lo que difiere con el presente estudio ya que los estudiantes de la UPSJB presentan una actitud negativa frente a los portadores, por lo cual se debería aumentar en el plan de estudios para tener una mejor actitud.…”
Section: (Tabla 5)unclassified
“…En el 2017, Sheth y col. 15 evaluaron el nivel de conocimiento de los estudiantes de odontología sobre el VIH/SIDA. Participaron voluntariamente 267 estudiantes de 3º, 4º año y pasantes de BDS de AMC Dental College and Hospital, para esta encuesta se diseñó un cuestionario cerrado con preguntas de opción múltiple y se utilizó la prueba de chi-cuadrado para el análisis estadístico con el software SPSS versión 20.…”
Section: Introduccionunclassified